Community Participation in Flood Disaster Management: Partisipasi Masyarakat dalam Penanggulangan Bencana Banjir - Makhfud; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2024)
General background disaster management requires active community participation to reduce disaster risks. Specific background this study focuses on community participation in flood disaster management in Balonggabus Village, Candi. Knowledge Gap Although many studies discuss community participation in disaster management, research examining local context and specific community participation is still limited. Aims this research to analyze the role and participation of the community in flood disaster management. Results show active participation from the community in cleaning drainage and awareness to engage in disaster management efforts. The community actively participates from the planning stage to the evaluation of disaster management programs. Novelty this study highlights the importance of involving various actors, including the government and the community, in disaster management and strengthens the concept of participation in the local context. Implications these findings can serve as a reference for government policies and related organizations to enhance disaster management programs by more effectively involving the community in the decision-making process. Highlights: Community awareness and participation are crucial for effective flood management. Collaboration between government and community enhances disaster preparedness and response. Research emphasizes the importance of local context in disaster management strategies. Keywords: Participation, Disaster, Management, Community, Research